Klinično ocenjevanje aktivnih stabilizacijskih mišic hrbtenice po metodi dinamične živčnomišične stabilizacije - Kurila, Peter (Rehabilitacija (Ljubljana), 2011)
Dynamic neuromuscular stabilization (DNS) is a relatively new concept for conservative treatment of patients with vertebral pathology. It was developed in the second half of the 1990-ies in Prague under the leadership of prof. Kolar, a disciple of prof. Lewit and the late prof. Vojta. The article describes some tests used to assess the stabilizing function of the spine by the DNS method. Since the DNS method has a broad theoretical basis, the article presents only some basic information.
Keywords: bolečina; hrbtenica; mišice; stabilizacija; therapy; vzorec dihanja; zdravljenje